2014
DOI: 10.1089/ten.tea.2013.0588
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization, Invasion, and Turnover Are Differently Influenced by Healthy and Tumor-Derived Extracellular Matrix

Abstract: The interplay between tumor cells and the microenvironment has been recognized as one of the hallmarks of cancer biology. To assess the role of extracellular matrix (ECM) in the modulation of tissue homeostasis and tumorigenesis, we developed a protocol for the purification of tissue-derived ECM using mucosae from healthy human colon, perilesional area, and colorectal carcinoma (CRC). Matched specimens were collected from the left colon of patients undergoing CRC resection surgery. ECMs were obtained from tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 52 publications
5
71
0
Order By: Relevance
“…Recent evidence has suggested that tumor-related extracellular environment may play a leading role, and it is not just a supporting actor over the initiation of the tumor; indeed, the dysregulation of the composition4 and stiffness21 of the ECM are associated with both the lack of asymmetric cellular division and of the differentiation of stem cells, and with the epithelial-mesenchymal transition of cancer stem cells as well, thus regulating tissue homeostasis and sustaining the onset and progression of cancer419. In agreement with these latter observations, we recently reported that an increased organization of ECM fibrils, but not biochemical composition, of the perilesional area of the colorectal carcinoma22 is associated with proliferation and infiltration of metastatic cancer cells23.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Recent evidence has suggested that tumor-related extracellular environment may play a leading role, and it is not just a supporting actor over the initiation of the tumor; indeed, the dysregulation of the composition4 and stiffness21 of the ECM are associated with both the lack of asymmetric cellular division and of the differentiation of stem cells, and with the epithelial-mesenchymal transition of cancer stem cells as well, thus regulating tissue homeostasis and sustaining the onset and progression of cancer419. In agreement with these latter observations, we recently reported that an increased organization of ECM fibrils, but not biochemical composition, of the perilesional area of the colorectal carcinoma22 is associated with proliferation and infiltration of metastatic cancer cells23.…”
supporting
confidence: 82%
“…2b) and MIBC (Fig. 2c) were isolated according to our previously published protocol validated on the human colon23. The hematoxylin-eosin stained sections of the non-neoplastic urinary bladder showed the different cells layers: (i) mucosa, formed by transitional epithelium and lamina propria, and (ii) muscolaris propria, known as detrusor muscle, formed by three layers of smooth muscle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic matrices could also be regarded as the future of engineering tumor microenvironments, but the high number of biomaterials proposed in the literature need to be further optimized before being effectively applied in the tumor biology fields [128]. In effect, in the design of these matrices, several key factors should be taken into account, and, among them, landscape/ topography, fiber orientation, porosity (macro-, micro-, nanoscale conditioning), matrix viscoelasticity, matrix remodeling, and growth factors' and cytokines' binding sites.…”
Section: Mimicking the Ecmmentioning
confidence: 99%